Analysis of Strengthening IoT-Based Sustainable Agriculture Digital Literacy Through Empowering the Sendangsari Millennial Farmer Community - Wardono, Wardono; Abidin, Zaenal; Indriyanti, Dyah Rini; Suryonegoro, Bayu Murti; Setiawan, Agung; Wijaya, Ifan Badra; Putri, Marshanda Antika; Wahyuningtyas, Ratna; Sakinah, Zidna Nurus; Prihantoro, Irfan Fajar (Jurnal Abdimas, 2025)
Sendangsari Village, Purworejo Regency, has significant agricultural potential, but its utilization is not optimal due to low digital literacy among farmers and minimal application of modern technology. This condition poses challenges in supporting sustainable agriculture, so technology-based innovation is needed. This study aims to analyze the strengthening of digital literacy in sustainable agriculture through the application of the Internet of Things (IoT) in empowering the Sendangsari Millennial Farmer Community. The method used was a mixed method with a questionnaire instrument, pre-test and post-test, and plant growth measurements in IoT-based and manual fields. The results showed a significant increase in participant understanding, marked by a 17.77% increase in post-test scores from the pre-test score of 70.8. The application of IoT in the experimental field also resulted in more optimal growth of tomato, lettuce, and caisim plants compared to manual methods, and increased the confidence of millennial farmers in adopting technology. This study concluded that agricultural digital literacy can be strengthened through socialization, training, and practice of the application of the Internet of Things (IoT). Village institutional support, expanding internet access, and developing the capacity of young farmers are recommended to accelerate the transformation towards sustainable agriculture.